2016
DOI: 10.1007/978-3-319-42937-3
|View full text |Cite
|
Sign up to set email alerts
|

Cool Math for Hot Music

Abstract: of the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…As this study is devoted to symmetries in quantum models of static and dynamic tonal attraction, we first give a brief introduction into mathematical musicology (Balzano 1980, Mazzola 1990, 2002, Mazzola et al 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As this study is devoted to symmetries in quantum models of static and dynamic tonal attraction, we first give a brief introduction into mathematical musicology (Balzano 1980, Mazzola 1990, 2002, Mazzola et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…This fundamental principle of octave equivalence induces an equivalence relation of acoustic stimuli into pitch classes, or chroma (Parncutt 2011) which circularly wind up throughout different octaves. Western and also Chinese music divides this continuous pitch class circle into twelve distinguished tones, or degrees (Mazzola et al 2016), comprising the chromatic scale shown in Tab. 1.…”
Section: Elements Of Musicmentioning
confidence: 99%
See 1 more Smart Citation
“…Alexandroff 2012). For applying basic ideas of group theory to music (Balzano 1980;Mazzola 2002;Mazzola, Mannone, and Pang 2016), it is essential that there are certain operations that allow the transformation of tones into other tones. For instance, one can increase the tones by a certain number of steps 0, 1, 2, .…”
Section: Realistic Accounts To Tonal Attractionmentioning
confidence: 99%
“…We can make music out of a snail shell, a mathematical conchoid: the music reproduces the "getting closer" of the shell's spirals, through shortening of silence and approaching of the pitch. 11 In this sense, we are keeping the main idea of the conchoid from the domain of visuals to the domain of sounds, through an opportune mapping of its mathematical definition via a 3-component parametric equation [18,28]. We can explain the eventual analogies between mathematical steps and visual steps through crossmodal correspondences [38] and the identification of audiovisual objects [14], as well as gestural similarity [19].…”
Section: This Proof Sounds Good!mentioning
confidence: 99%